Journalism against disinformation. Process and structure of fact-checking verification reports - García-Marín, David (Infonomy, 2024)
Fact-checking is one of the main journalistic solutions against the disinformation challenge. In order for fact-checkers to perform their work efficiently, they need to base their action on the scientific method and the application of a verification systematic model to check false narratives. This article analyzes and describes the usual verification process carried out by these media institutions in the different phases of selection, execution and, above all, elaboration of the verification reports. The results of this journalistic work, published on the websites of these outlets, hybridize properties of different types of journalistic reports, but do not fit in neither of them. Therefore, the question is left open as to whether fact-checking is giving birth to a new journalistic genre (the fact-checking report) or simply reconfiguring some of the existing ones.